2018
DOI: 10.1038/s41598-018-32551-7
|View full text |Cite|
|
Sign up to set email alerts
|

Parkin-dependent regulation of the MCU complex component MICU1

Abstract: The mitochondrial Ca2+ uniporter machinery is a multiprotein complex composed by the Ca2+ selective pore-forming subunit, the mitochondrial uniporter (MCU), and accessory proteins, including MICU1, MICU2 and EMRE. Their concerted action is required to fine-tune the uptake of Ca2+ into the mitochondrial matrix which both sustains cell bioenergetics and regulates the apoptotic response. To adequately fulfil such requirements and avoid impairment in mitochondrial Ca2+ handling, the intracellular turnover of all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 70 publications
1
20
0
Order By: Relevance
“…The AKT-mediated MICU1 phosphorylation abolishes MICU1's gatekeeping function on MCU, leading to higher mitochondrial Ca 2+ content at resting conditions and ROS production [103] (Figure 2). We observed that phosphor-MICU1 accumulates in a non-mature form that is rapidly degraded (potentially by the ubiquitinproteasome system, as recently proposed [104]), leading to concomitant loss of the binding partner MICU2 and a disordered MCU complex composition [103]. The expression of a nonphosphorylatable MICU1 mutant restores normal mitochondrial Ca 2+ and ROS levels and inhibits AKT-mediated tumor growth in vivo, suggesting that the MICU1dependent regulation of mitochondrial Ca 2+ and ROS homeostasis is a crucial element in AKTdriven tumorigenesis.…”
Section: Mcu Complex and Tumor Progressionsupporting
confidence: 80%
“…The AKT-mediated MICU1 phosphorylation abolishes MICU1's gatekeeping function on MCU, leading to higher mitochondrial Ca 2+ content at resting conditions and ROS production [103] (Figure 2). We observed that phosphor-MICU1 accumulates in a non-mature form that is rapidly degraded (potentially by the ubiquitinproteasome system, as recently proposed [104]), leading to concomitant loss of the binding partner MICU2 and a disordered MCU complex composition [103]. The expression of a nonphosphorylatable MICU1 mutant restores normal mitochondrial Ca 2+ and ROS levels and inhibits AKT-mediated tumor growth in vivo, suggesting that the MICU1dependent regulation of mitochondrial Ca 2+ and ROS homeostasis is a crucial element in AKTdriven tumorigenesis.…”
Section: Mcu Complex and Tumor Progressionsupporting
confidence: 80%
“…Furthermore, our study confirms, as previously described, the involvement of parkin in the control of cellular Ca 2 + levels, suggesting altered interactions between the endoplasmic reticulum and the mitochondria, and a potential different efficiency for the main Ca 2+ transport mechanisms. An additional element to the link between parkin and mitochondria-related calcium homeostasis is provided by a recent study, showing that parkin selectively regulates the turnover of the MCU accessory protein MICU1 [77]. MICU1 is a regulatory subunit of the MCU complex that is found to exert a stimulatory effect on mitochondrial Ca 2+ uptake [78].…”
Section: Discussionmentioning
confidence: 99%
“…In basal conditions, Parkin was found to ubiquitylate MICU1, which is rapidly degraded via the proteasome system. In this way, Parkin indirectly also controls MICU2 levels, as MICU2 stability depends on MICU1 [102]. Even in this case, the Parkin Ubl domain is important for this action because the expression of a ∆Ubl Parkin mutant has no effect on MICU1 turnover.…”
Section: Int J Mol Sci 2020 21 X For Peer Review 7 Of 17mentioning
confidence: 99%